METHODOLOGY FOR DEVELOPING INFORMATION-ANALYTICAL COMPETENCE OF FUTURE ELEMENTARY SCHOOL TEACHERS - Meyliyev Sobir Xolmuradovich (Scholar Express Journal, 2023)
The article substantiates the methodology for the development of information and analytical competence of future primary school teachers. An essential role in the preparation of future primary school teachers is occupied by activity and project methods, methods of heuristic teaching
Keywords: : professional competence; variability of education; modeling of professional activity; future primary school teachers